FAKTOR-FAKTOR PENDORONG KALANGAN REMAJA MENGKONSUMSI MINUMAN KERAS DI KELURAHAN WAY HALIM PERMAI KECAMATAN SUKARAME KOTA BADAR LAMPUNG - Riadi, Slamet; Damayantie, Anita (SOCIOLOGIE, 2013)
The purpose of this study was to determine the factors that drives teens to consume alcohol and to know how teen promiscuity in villages Way Halim Permai keamatan Sukarame Bandar Lampung. The research is qualitative. Informants from the community, officials who have been determined based on purposive sampling technique according to the needs of research. The results in this study are among the causes of teenage drinking yag views of the individual factors which liquor by a juvenile can eliminate the problem and promising pleasure and want to know who has a high action and trial and error. Viewed from external factors, namely family factors seen from the lack perhatia, supervision, religious education, the economy and the direction of the parents, social factors impressionable teenagers and the pressure from my existing theme environment.Keywords: Determine the factors, teens, consume alcohol